Determinan Variabel Demografi Terhadap Cerai Hidup Wanita Di Pulau Sumatera: Survei Demografi Dan Kesehatan Indonesia 2017 - Angga Setyawan (LP2M, 2021)
The purpose of this study was to analyze the demographic variables that affect the probability (chance) of divorce for women on the island of Sumatra. This research is a quantitative analysis, using secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS) with logistic regression analysis method. The results showed that three variables that significantly influence the high and low chance of divorce for women are wife's education, number of children and wife's occupation. The wife's education has a significant effect on the chance of a woman's divorce, with the wife's education coefficient is positive, which means that the lower the wife's education, the higher the chance for a wife to be divorced. The coefficient value of the number of children is positive, which means that the fewer children (</= 2 children), the higher the chances of women experiencing divorce. The wife's occupation variable shows a negative coefficient, which means that a wife who works as an informal worker has a lower chance of experiencing divorce than a wife who works as a formal worker. Meanwhile, the age at first marriage variable does not significantly affect the chances of a woman's divorce.